Regulating tobacco - Rabin, Robert L.; Sugarman, Stephen D. (Oxford ; New York : Oxford University Press, 2001)
This collection includes essays by 11 leading public health experts, economists, physicians, political scientists, and lawyers, whose activities encompass Congressional testimonies, Surgeon General's reports on youth smoking, and clinical trials for drugs for smoking cessation. They analyze specific strategies that have been used to influence tobacco use, including taxation, regulation of advertising and promotion, regulation of indoor smoking, control of youth access to cigarettes and other tobacco products, litigation, and subsidies of smoking cessation, and set them against the scientific findings about tobacco and the changing cultural and political setting against which policy decisions are being made.; This book is intended for scholars, lawyers, policy-makers, anti-tobacco activists, those interested in the development of tobacco regulations.
The politics of tobacco regulation in the United States / Robert A. Kagan & William P. Nelson -- Taxing tobacco: the impact of tobacco taxes on cigarette smoking and other tobacco use / Frank J. Chaloupka, Melanie Wakefield, & Christina Czart -- Marketing policies / John Slade -- Reducing harm to smokers: methods, their effectiveness, and the role of policy / Kenneth E. Warner -- Reducing the supply of tobacco to youths / Nancy A. Rigotti -- The third wave of tobacco tort litigation / Robert L. Rabin -- Clean indoor air restrictions: progress and promise / Peter D. Jacobson & Lisa M. Zapawa -- International aspects of tobacco control and the proposed WHO treaty / Stephen D. Sugarman.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Tobacco industry -- Government policy -- United States; Cigarette industry -- Government policy -- United States; Tobacco use -- Health aspects -- United States; Tobacco use -- Prevention -- Government policy -- United States; Cigarette smoke -- Health aspects -- United States; Advertising -- Cigarettes -- Government policy -- United States; Youth -- Tobacco use -- Prevention -- Government policy -- United States; Medical policy -- United States; Tobacco industry -- Law and legislation -- United States; Smoking -- Law and legislation -- United States; Tabac -- Industrie -- Politique gouvernementale -- États-Unis.; Cigarettes -- Industrie -- Politique gouvernementale -- États-Unis.; Cigarettes -- Publicité -- Politique gouvernementale -- États-Unis.; Politique sanitaire -- États-Unis.; SELF-HELP -- Substance Abuse & Addictions -- General; PSYCHOLOGY -- Psychopathology -- Addiction; Advertising -- Cigarettes -- Government policy; Cigarette industry -- Government policy; Cigarette smoke -- Health aspects; Medical policy; Smoking -- Law and legislation; Tobacco industry -- Government policy; Tobacco industry -- Law and legislation; Tobacco use -- Health aspects; United States